PERAN TRUST DALAM MEMEDIASI PENGARUH GREEN MARKETING DAN PRODUCT QUALITY TERHADAP PURCHASE DECISION (Studi pada Konsumen Mi Lemonilo) - Muzayyanah, Siti; Soliha, Euis (Komunitas Manajemen Kompetitif, 2025)
This study aims to examine the role of trust as a mediating variable in the relationship between green marketing and product quality on consumer purchasing decisions for Mi Lemonilo. This research is motivated by increasing public awareness of the importance of products that support a healthy and sustainable lifestyle, so that companies are required to implement green marketing strategies and maintain optimal product quality to build trust and encourage consumer purchasing decisions. The approach used in this study is quantitative with the Partial Least Square–Structural Equation Modeling (PLS-SEM) data analysis method. The results show that green marketing and product quality have a positive and significant influence on trust and purchasing decisions. In addition, trust is proven to be able to mediate the influence of green marketing and product quality on purchasing decisions, thereby strengthening the relationship between these variables. This research provides strategic implications for companies in designing green marketing strategies, improving product quality, and building consumer trust to improve purchasing decisions. Keywords: green marketing, product quality, trust, purchase decision